1998
DOI: 10.1128/jcm.36.7.1953-1958.1998
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Stenotrophomonas maltophilia Isolated from Clinical Specimens from Patients with Cystic Fibrosis and Associated Environmental Samples

Abstract: Stenotrophomonas maltophilia was isolated from the respiratory tracts of 41 (25%) of 163 children attending our pediatric cystic fibrosis unit between September 1993 and December 1995. The extents of S. maltophilia contamination of environmental sites frequented by these patients were investigated with a selective medium incorporating vancomycin, imipenem, and amphotericin B. Eighty-two isolates of S. maltophilia were cultured from 67 different environmental sites sampled between January and July 1996. The org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(87 citation statements)
references
References 39 publications
2
80
0
5
Order By: Relevance
“…Several studies reported that the incidence of S. maltophilia infection in CF has also increased in recent years (16,85,195,305). Data from the CFF Patient Registry support this, indicating that the prevalence of S. maltophilia increased from 4.0% in 1996 to 12.4% in 2005, with the highest rates of infection (15.8% in 2005) occurring for adolescents 11 to 17 years old (72,249).…”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies reported that the incidence of S. maltophilia infection in CF has also increased in recent years (16,85,195,305). Data from the CFF Patient Registry support this, indicating that the prevalence of S. maltophilia increased from 4.0% in 1996 to 12.4% in 2005, with the highest rates of infection (15.8% in 2005) occurring for adolescents 11 to 17 years old (72,249).…”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 92%
“…The inappropriate use of hand moisturizing lotion instead of soap by a health care worker was associated with infection among bone marrow transplant recipients in one center (159), while in another center, contamination of faucet aerators in intensive care unit sinks was implicated as the source of S. maltophilia infection (343). Other studies also reported the recovery of this species from hospital sink drains, faucets, and potable water (84,85). However, genotyping analyses typically have not provided a link between isolates obtained from such hospital environmental sources and those recovered from patients (84,197).…”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrate long-term persistence within biofi lm adherent to hospital plumbing components and other water-exposed sites. 14,15 Most respiratory viruses such as coronavirus, rhinovirus and infl uenza can survive on dry surfaces for a few days, with gastrointestinal viruses retaining viability for a couple of months. Norovirus is found in the hospital environment for days after an outbreak, demonstrating survivability despite terminal cleaning with bleach-based products.…”
Section: Pathogen Survival Time In the Hospital Environmentmentioning
confidence: 99%
“…and Stenotrophomonas are associated with damp places such as taps, sinks, showers and baths. 1,13,15,26,27 Coliforms such as Klebsiella and Serratia have been identifi ed from buckets, bowls, mops and liquids. 1,28 Thus, traditional sites for Gram-negative microbes have been sites constantly or intermittently exposed to water, but this is not always the case.…”
Section: Identifying the Main Reservoirs Of Microorganismsmentioning
confidence: 99%